We Make Spirit by Walking: An Application of Kovel’s Spirituality to the Life and Work of Committed Environmentalists - Barbara McDonald (Adult Education Research Conference, 2002)
This paper employs Kovel’s (1991) five meditations on spirit as an analytical framework for exploring the spirituality of committed environmental activists. These meditations explicitly present spirituality as the making of spirit, that is, as bringing spirit power into one’s life through learning and doing.